Does Productive Zakat Affect the Growth of Mustahiq Micro Business? Case Study Lazismu DIY - Dwi Santosa Pambudi; Rofiul Wahyudi; Alung Prasetya; Ketina Widiana; Rasyid Bimo Radithyo; Dhea Arsy Ramadhini; Inda Dwi Kartika (Universitas Ahmad Dahlan, 2024)
Introduction: State the problem statements of the article briefly and concisely. One of the pillars of Islam that has an economic dimension is zakat, where the funds collected can be utilized with the aim of increasing the growth of the mustahiq business. In contemporary treasures, it is called the utilization of productive zakat. Purpose: The purpose of this study is to explore the relationship between the utilization of productive zakat in increasing the growth of Mustahiq Business in the Muhammadiyah Amil Zakat Institute (LAZISMU) Yogyakarta. Methodology: This study uses a quantitative method with a descriptive approach and data analysis using linear regression. Data was collected from mustahiq who received productive zakat from LAZISMU Yogyakarta. Findings: The finding is that the utilization of productive zakat has a significant and positive impact on the growth of mustahiq businesses, both partially and simultaneously. Paper Type: Research Article or General Review Keywords: Growth; Lazismu; Micro Business; Productive Zakat